GE_GERICHTE P/11053/2021 vom 17. Januar 2025 - GE Cour de justice (2025)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE;RECTIFICATION DE LA DÉCISION;MISE EN LIBERTÉ DÉFINITIVE | CP.180; LStup.19; LStup.19; LStup.19; CP.139; LCR.90; CP.123; LStup.19a; CP.43; CPP.83.al1